The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ehf2.13121
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle atrophy in heart failure with diabetes: from molecular mechanisms to clinical evidence

Abstract: Two highly prevalent and growing global diseases impacted by skeletal muscle atrophy are chronic heart failure (HF) and type 2 diabetes mellitus (DM). The presence of either condition increases the likelihood of developing the other, with recent studies revealing a large and relatively poorly characterized clinical population of patients with coexistent HF and DM (HFDM). HFDM results in worse symptoms and poorer clinical outcomes compared with DM or HF alone, and cardiovascular‐focused disease‐modifying agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 133 publications
(298 reference statements)
3
29
0
Order By: Relevance
“…Diabetes and heart failure synergistically contribute to severely decreased physical function through skeletal muscle atrophy, inflammation, and metabolic dysfunction. 21 Levels of cardiac dysfunction may correlate poorly with symptoms, 22,23 and exercise training, although associated with improved physical function, 6 has relatively little effect on cardiac function in heart failure. 24,25 The benefits of physical rehabilitation and exercise are thought to be primarily through peripheral mechanisms such as improved skeletal muscle, mitochondrial, and microvascular function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes and heart failure synergistically contribute to severely decreased physical function through skeletal muscle atrophy, inflammation, and metabolic dysfunction. 21 Levels of cardiac dysfunction may correlate poorly with symptoms, 22,23 and exercise training, although associated with improved physical function, 6 has relatively little effect on cardiac function in heart failure. 24,25 The benefits of physical rehabilitation and exercise are thought to be primarily through peripheral mechanisms such as improved skeletal muscle, mitochondrial, and microvascular function.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle strength among heart failure patients with diabetes is impaired compared with patients without diabetes, 28 potentially as a result of mitochondrial dysfunction, reactive oxygen species generation, insulin resistance, lipotoxicity, and inflammation. 21 Other complications of diabetes can lead to significant impairments in mobility and physical function. Patients with diabetes often have concurrent peripheral neuropathy, which can impair balance and proprioception, leading to reduced functional performance and stability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the serum cystatin C level might be elevated by an increase in the BMI, possibly through subclinical inflammation ( 10 , 19 - 21 ) but not a decline in the renal function, leading to discordance between eGFRcre and eGFRcys. In addition, muscle wasting is frequently observed in patients with DM, regardless of increased fat mass, which is called sarcopenic obesity; this effect contributes to the co-existence of a reduced Scr level and increased body weight ( 23 - 25 ). Importantly, a reduction in hemoglobin levels and elevation in BUN levels, markers of malnutrition, are not typically found at this stage of DM if patients do not have advanced-stage diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the utility of the eGFR for assessing the renal function in diabetic patients is a matter of debate ( 25 ). The results of a cross-sectional study by Luis-Lima et al showed that there was poor agreement between eGFRcre or eGFRcys and the GFR measured by the plasma clearance of iohexol (“measured GFR”), which was greater in patients with a measured GFR <60 mL/min, leading to misclassification of CKD stages in approximately 30% of the study subjects ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many metabolic diseases, including diabetes, chronic kidney disease, and cancer, can cause whole-body muscle atrophy and make people become emaciated [ 34 , 35 ]. This situation can not only lead to the loss of body muscle mass, but also increase the mortality of humans.…”
Section: Discussionmentioning
confidence: 99%